Depleted uranium munitions and the Ukraine war: a warning against DU renaissance - Eslami, Mohammad; Vieira, Alena; Al-Marashi, Ibrahim (Frontiers in Political Science, 2024)
Contrary to the contested use of depleted uranium (DU) weapons following the Iraq war in 2003, which led some nations to seek a ban on DU use and even eliminate their existing arsenals, there is now a growing tendency both toward the use and production of DU weapons, rendering such weapons as “normal” and “acceptable.” There is a risk of a DU renaissance as a consequence of the war in Ukraine. We argue that more attention is needed to the strategies to deal with the DU renaissance, including further research on the health and environmental effects and the associated clean-up efforts, particularly concerning chemical toxicity and exposure to DU-linked radiation, to the alternative military strategies, as well as alternative munitions, such as tungsten.